Empirical evidence of IFRS studies in Indonesia - Dwi Ernawati; Y. Anni Aryani (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2019)
This study aims to provide empirical evidence about the development of International Financial Reporting Standards (IFRS) study in Indonesia. This study analyzes thirty one IFRS articles derived from eight accredited national journals with observation period 2008-2017. We classify articles based on topics and research methods used, and then do mapping approach (charting the field). This study found financial statements quality is the most frequently researched topics. In addition, we also found research gaps on IFRS adoption and financial statement quality that were proxied by earning management and relevance. Evidently, the result of previous study is still not consistent. In addition, the previous research of IFRS adoption and the quality of financial reporting were carried out at the early phase of IFRS adoption so that it still needs to be examined how about the impact of IFRS adoption on the quality of financial reports in the next phase.